Two Portrait Stelae from Roman Epidaurum (Archaeologia Adriatica, 2008)
This article discusses the fragments of two funerary stelae with portraits of the deceased, originally from Roman Epidaurum (Cavtat). One fragment (I), today in the Kunsthistorisches Museum in Vienna, depicts the figure of a Roman signifer (standard bearer) at life size and in full battle dress (Fig. 1). He is clothed in a tunic and paenula (tunica, paenula), with two belts around his waist (baltei), and with caligae on his feet. The paenula is draped like a sagum or paludamentum to enable depiction of the weapons hung from the belts – a sword on the left (gladius) and a dagger on the right (pugio). On his head was a helmet made from an animal scalp. Held in his left hand is a small ellipsoid shield (scutum) with one pointed end leant against the left flank. His right hand cannot be seen as it holds the signum. The standard has a sharpened lower end, and it is decorated with elongated rectangular platelets with rounded edges, a medallion in the form or a wreath or a phalera with a male bust, a wreath (corona), and a standard (vexillum). The architrave and tympanum were removed during the secondary reworking of the monument. The tympanum would definitely have been triangular, formed fully or inscribed in the rectangular terminal of the monument. The inscription would likely have been in the missing lower section. On the basis of the analysis of the portrait of the deceased, the segment of the bust that is displayed in the medallion, and the fashion of wearing two belts, the author dates the stele to the very end of the 1st century or the beginning of the 2nd century, i.e. most probably in the period of Trajan, and possibly in the first years of the reign of Hadrian.The second stele is displayed in the Baltazar Bogišić Collection in Cavtat (II). All that is left is in fact just a small piece of its upper section, broken off at the top of the inscription field, but its original appearance can easily be reconstructed (Fig. 2). The bust of an older woman is depicted in the tympanum. Other than a dedication to the Manes, the inscription is not preserved. On the basis of an analysis of the hairstyle the workmanship of the stele is dated to the third or fourth decade of the 3rd century BC.
Keywords: stelae; portraits; signifer; pallium